Levantamento taxonômico de Fabaceae Lindl. em um afloramento granítico do semiárido brasileiro - Rodrigues, Erimágna de Morais (2018)
Fabaceae is one of the most numerous angiosperm families in the world, with cosmopolitan distribution; being found from the Alps to the plains. In the Caatinga biome, it is the most taxonomically diverse, even in rocky outcrops. Over the years, the family has undergone numerous changes in its classification and recent phylogenetic studies have shown that some of its genera are paraphyletic, which resulted in the establishment of six subfamilies for Fabaceae. This work aimed to present a floristic-taxonomic study of Fabaceae, in a rocky outcrop situated in the semi-arid region of Paraiba, Brazil. Biweekly collections were made throughout the rocky outcrop, through random walks, from May / 2016 to June / 2017, for the collection of botanical material in the reproductive stage. The samples obtained in the field were dried according to the conventional recommendations in vegetal taxonomy and incorporated in the Manuel Arruda Câmara Herbarium (ACAM), of the State University of Paraíba (UEPB), Campus I, Campina Grande. Taxon identifications were based on the family bibliography as well as specialist consultations. Twenty - eight species belonging to three subfamilies: Caesalpinioideae (12 spp.), Detarioideae (01 sp.) and Papilionoideae (15 spp.) were recognized. Among the species found, two of them constitute new records for the state of Paraíba, Ancistrotropis peduncularis and Crotalaria pallida. The treatment includes taxonomic descriptions, key for genera and species, flowering data and fruiting and geographic distribution, as well as photographic records of the species found.